Non-radiative Auger Current in a InGaN/GaN Multiple Quantum Well Laser Diode under Hydrostatic Pressure and Temperature - Rajab Yahyazadeh; Zahra Hashempour (Journal of Optoelectronical Nanostructures, 2023)
Abstract: This study employs a numerical model to analyze the non-radiative Auger current in c-plane InGaN/GaN multiple-quantum-well laser diodes (MQWLD) under hydrostatic pressure and temperature. Finite difference methods (FDMs) were used to acquire energy eigenvalues and their corresponding eigenfunctions of InGaN/GaN MQWLD. In addition, the hole eigenstates were calculated via a 6*6 k.p method under applied hydrostatic pressure and temperature. The calculations demonstrated that the hole-hole-electron (CHHS) and electron-electron-hole (CCCH) Auger coefficients had the largest contribution to the total Auger current (76% and 20%, respectively). Increasing the hydrostatic pressure could increase the amount of the carrier density and the electric field. On the other hand, this increase reduced the overlap integral of wave functions and the localized length of electrons, heavy, light and split of band holes. Also, for the hydrostatic pressure of about 10 GPa and the temperature ‎‎of 300 K, the non-radiative Auger current has an optimum value of 334 A/cm2. ‎The results reveal that the elevated hydrostatic pressure and temperature play a positive and negative role in the performance of laser diodes.